ASPEK SOSIAL BUDAYA DAN LINGKUNGAN FISIK MASYARAKAT SUKU DA’A DALAM KAITANNYA DENGAN KEJADIAN MALARIA DI WILAYAH KOTA PALU SULAWESI TENGAH - -, Ningsi; Erlan, Ahmad; -, Puryadi (Media Penelitian dan Pengembangan Kesehatan, 2011)
The study had conducted on Da'a community residing in Selena hamlet, Buluri village West Palu district. The ethnic community is Da?a Kaili comunity who still holds  cultural values in their daily behavior. This study used quantitative and qualitative methods. Most of the comunities are traditional  farmers with the income less than Rp. 500 000/month. Knowledge level of the respodents related to disease symptoms, transmittion and how  prevention. The behavior of respondents had indicated a positive attitude especially their seeking treatments behavior but they still have negative behavior like their outside actvities during the night. Their prevention behavior againts mosguito bites is still low but on the ofther hand they have positive attitude like they agreed ti use PPE (Personal Protective Equipment) when sleeping during the night. The comunity still had traditional beliefe of ilnee causing and how to prevent it by using their traditional ceremonies of healing ang pain avoiding. The residential area are surrounded by mountains, forests, bushes and the river which could be risk to malaria it bady supported with their housing conditions which, mostly made of bamboo.